Identifying molecular signatures of post-traumatic stress disorder vulnerability and progression in a longitudinal study: a study protocol - Suprani, Federico; Paribello, Pasquale; Mancini, Giulia Federica; Morena, Maria; Pinna, Marco; Pinna, Federica; Contu, Martina; Visioli, Caterina; Medas, Fabio; Canu, Gian Luigi; Cappellacci, Federico; Calò, Pietro Giorgio; et al. (Frontiers in Psychiatry, 2025)
Post-Traumatic Stress Disorder (PTSD) is a highly debilitating psychiatric disorder, which develops in a subset of trauma-exposed individuals. Patients with PTSD fail to extinguish fear responses to no-longer dangerous stimuli and develop enduring experiences of fear and anxiety. To advance the understanding of PTSD neurobiology, longitudinal and comprehensive clinical and molecular data are needed. Here we present the protocol of the project “Reli€ving-PTSD” aiming at identifying the molecular signatures of PTSD vulnerability and disease progression in a longitudinal study in humans. The molecular signature will be based on the analysis of the endocannabinoid (eCB) system, as well as miRNome and transcriptome profiles. The study will recruit 60 participants hospitalized in the Intensive Care Unity of the University Hospital Agency of Cagliari. Participants will be eligible for this study if they are: 1) between 18 and 65 years old; 2) able to provide written informed consent. We plan to recruit 30 patients with a diagnosis of PTSD or Acute Stress Disorder (ASD) according to DSM-5 and 30 patients without either diagnosis. Exclusion criteria are: 1) history of traumatic brain injury; 2) current and/or lifetime diagnosis of psychiatric disorders other than PTSD/ASD; 3) current and/or lifetime diagnosis of substance use disorder; 4) presence of severe neurological or medical morbidity. These stringent eligibility criteria will reduce the confounding effect of comorbidities, as molecular alterations of the eCB system have been associated to several psychiatric disorders. This research addresses critical gaps in PTSD management. The outcomes are anticipated to significantly advance scientific knowledge, inform clinical practices, and benefit public health by reducing the societal and economic burden of PTSD through improved precision medicine-based prevention and treatment strategies. The study was reviewed and approved by the Ethics Committee of the Region of Sardinia (Prot. CE/2023_014) and funded by the European Union - Next Generation EU - NRRP M6C2 - Investment 2.1 Enhancement and strengthening of biomedical research in the NHS.